Historical Sustenance Style and Social Orientations in China: Chinese Mongolians Are More Independent Than Han Chinese - Stojcic, Ivana; Wei, Qingwang; Ren, Xiaopeng (Frontiers in Psychology, 2020)
In this study, we examined the Chinese Han and Mongolian, two ethnic groups that belong to the same national and geographic regions but vary in their degrees of social interdependence and independence. We assumed that the Mongolian, who have traditionally been known as a herding community, exhibit a greater independent social orientation compared to the Han Chinese, who have traditionally been known as an agrarian community. Through three different studies we used the explicit measurement of self-construal, implicit cultural task of self - inflation and the practice of name-giving (i.e., baby names as a cultural product) to test our hypothesis. The obtained results revealed that compared to Han Chinese, Mongolian scored higher on independent –self subscale, had greater levels of self-symbolic inflation and were less likely to give common names to their babies. These findings suggest that Mongolians are more independent than Han Chinese. In view of that, the present study contributes to a better understanding of the complexity of Chinese culture in terms of interdependence and independence, and provides further support for historical sustenance theory.